KARAKTERISTIK SORPSI DAN DESORPSI FOSFAT PADA OXISOL DENGAN PENDEKATAN KINETIK - Mimien Hariyanti (Jurusan Tanah Fakultas Pertanian Universitas Andalas, 2010)
The phosphorous sorption and desorption characteristics were studied in Oxisols Padang Siantah West Sumatera. The amount of P (0, 20, 40, 80, 100, 200, 400, 800 g P) was added to 1 gram soil and incubated for 0.04 days (1 hour) , 0.125 days (3 h), 0.25 days (6 h), 0.375 days (9 h), 1,3, 6, 9, 18 dan 36 days. A completely factorial design in triple replication was set up. The results of P sorption and desorption experiment showed that Oxisol had very high sorption with time until 99 from added P. P desorption maximum at the time was 3 days with sorption value 1,67 % from added P. Keywords : Oxisol, Fe and Al oksides, P sorption, P desorption, time of reaction.